Hepatitis B and C seroprevalence in patients with diabetes mellitus and its relationship with microvascular complications - Kadir Gisi; Ali Cetinkaya; Mesut Ozkaya; Bulent Kantarceken; Gokce Gisi; Sedat Koroglu (Gastroenterology Review)
Introduction: Diabetic patients are susceptible to bacterial, viral and fungal infections because of various deficiencies in the immune system. Aim: To investigate a possible link between hepatitis B/C prevalence and microvascular complications as well as duration of diabetes. Material and methods: In total 1263 diabetic patients (1149 type 2, 114 type 1) were enrolled in the study. The control group consisted of 1482 healthy blood donors who were over 40 years old. All diabetic patients were tested for HBsAg, anti-HBs and anti-HCV beside routine laboratory tests. Diabetic patients were divided into three groups according to their diabetes duration, and all of the patients were scanned for microvascular complications. Demographic data of all patients were recorded. Results : HBsAg seropositivity was 3.7% in diabetic patients and 1.08% in the control group; this difference was statistically significant (p < 0.001). HBsAg positivity rates in type 1 and type 2 diabetics were 0.8% and 4%, respectively (p = 0.09). HCV seropositivity was 2.2% for diabetics and 0.5% for the control group; this difference was statistically significant (p 0.05). Also, no relationship was found between microvascular complications of diabetes and hepatitis B/C seropositivity. Conclusions : Hepatitis B and C seroprevalence was found to be increased in diabetes mellitus; however, there was no relationship between hepatitis seroprevalence and the duration or microvascular complications of diabetes.